1982
DOI: 10.1002/ana.410120506
|View full text |Cite
|
Sign up to set email alerts
|

Selective reduction of blood flow to white matter during hypotension in newborn dogs: A possbile mechanism of periventricular leukomalacia

Abstract: The cerebrovascular response of newborn animals to hypotension has not been defined on a regional basis. Using an autoradiographic technique employing 14C-iodoantipyrine as indicator, we studied the cerebral physiological responses of newborn dogs to hypotension induced by exsanguination or by administration of Escherichia coli endotoxin. Regional cerebral blood flow (rCBF) to all gray matter structures was preserved, even at mean arterial pressures as low as 20 mm Hg. In contrast, rCBF to periventricular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(10 citation statements)
references
References 12 publications
3
7
0
Order By: Relevance
“…This is in agreement with a previous study, which showed that blood flow to many areas of white matter was impaired during severe systemic hypotension in young dogs, but blood flow to all gray matter areas was preserved. 8 A similar observation was also made in ischemic leukoaraiosis. 7…”
Section: Discussionsupporting
confidence: 64%
“…This is in agreement with a previous study, which showed that blood flow to many areas of white matter was impaired during severe systemic hypotension in young dogs, but blood flow to all gray matter areas was preserved. 8 A similar observation was also made in ischemic leukoaraiosis. 7…”
Section: Discussionsupporting
confidence: 64%
“…Several models of inflammatory postnatal brain injury have been developed in different species, including mouse ( 52 56 ), rat ( 57 59 ), rabbit ( 60 , 61 ), dog ( 62 ), and others ( 63 ). Rodent models are most widely used due to ease of use and relatively short reproductive cycle.…”
Section: Il-1ra and Pathogenic Models Of Postnatal Brain Injurymentioning
confidence: 99%
“…TLR-4 receptors were found in the immature brain, and LPS administration induced an increased expression of CD14 [69]. In addition to the inflammatory response [91,92], LPS induces hypoperfusion [93], hypoglycemia [93], hyperthermia [91] and lactic acidosis, which may important factors triggering brain damage. In fact, a high dose of LPS (12 mg/kg) induced hypotension (50% decrease) as well as decrease in cerebral blood flow (CBF) in white matter, suggesting that hypoperfusion is an important contributor to injury in this region [93].…”
Section: Animal Models Of Pvlmentioning
confidence: 99%